Aonla rust, its causes, epidemiology and management- A review (IASH Indian Journal of Arid Horticulture, 2024)
Aonla or Indian Gooseberry is an important fruit crop grown in the Indian sub continent, celebrated for its exceptional nutritional and rejuvenating properties and highly valued in Unani and traditional Indian medicine for its medicinal benefits. However, Aonla rust caused by the fungus Ravenelia (Phakopsora) emblicae, poses significant threat to productivity of this fruit crop as it can severely impact crop yield and quality, leading to economic losses for farmers. This fungal disease thrives in warm, humid conditions and is exacerbated by factors such as improper planting density and poor water management. The effects of Aonla rust include reduced fruit production, lower fruit quality, and overall tree health decline, ultimately affecting the economic viability of Aonla farming. Effective management of Aonla rust involves a combination of cultural practices, chemical treatments, use of bioagents and the use of resistant varieties. The common chemical treatment interventions involve foliar application of wettable sulphur / Mancozeb 75 WP/ Chlorothalinil @ 0.2% and Copper oxychloride 50 WP @ 0.3% at 10-12 days’ intervals starting in August. Bio agents such as Trichoderma harzianum and Pseudomonas fluorescens and organic pesticides like neem oil, NSKE, and neem leaf extract have also been proven effective in disease control. Strategies such as proper spacing, pruning, and the application of fungicides are essential in disease management. Additionally, the development and use of rust-resistant Aonla varieties is crucial for sustainable production. Ongoing research and integrated disease management approaches will be key to mitigating the impact of Aonla rust and ensuring the continued success of Aonla cultivation.